Study of spin-isospin response of 11Li neutron-drip-line nucleus with PANDORA. (December 2020) - Stuhl, L.; Sasano, M.; Gao, J.; Hirai, Y.; Yako, K.; Wakasa, T.; Ahn, D. S.; Baba, H.; Chilug, A. I.; Franchoo, S.; Fujino, Y.; Fukuda, N.; et al.
Abstract: The spin-isospin responses of the 11 Li drip-line nucleus has been measured. Preliminary results of the 11 Li( p, n ) 11 Be experiment in inverse kinematics at RI Beam Factory (RIBF) of RIKEN Nishina Center are presented including the observation of 1 n, 2 n, t, d, 2 α and 6 He+ α decay channels of 11 Be reaction product. Details of the experimental setup based on PANDORA (Particle Analyzer Neutron Detector Of Real-time Acquisition) low-energy neutron detector and the SAMURAI large-acceptance magnetic spectrometer are described.